Information Retrieval Pemetaan Peta Jalan Penelitian Perguruan Tinggi Berbasis Dokumen Publikasi Ilmiah Dosen - Agung Wibowo; Rusda Wajhillah (Jurnal Larik: Ladang Artikel Ilmu Komputer, 2022)
The quality of research needs to be directed and classified for improvement. A college roadmap must accordance interest and expertise from it lecturers. Therefore, be the duty of every college to create a strategic plan and pre-eminent research. Faculty of information technology in most all College has produced many scientific publications. Publication document of scientific papers is one example of unstructured documents. Its contents form of writing style, mostly defined by the author language. Generally, the document title only determined the maximum number of words. The main objective of the information retrieval system is to determine the documents keywords from the query provided by the user in a group of documents. TF/IDF Algorithm (Term Frequency – Inversed Document Frequency) and the Vector Space Model algorithm is several methods of the algorithm that can utilize on text mining in analysing phases as options document classification determination-based solutions words that often appear on the document title. This paper can help decision makers to determine, assess, adapt research roadmap to College. The depiction of a tree model using long-term roadmap makes it easier to read and understand.